2021
DOI: 10.3390/ijms222212154
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Presepsin (P-SEP) in the Diagnosis of Sepsis in the Critically Ill Infant: A Literature Review

Abstract: Sepsis causes high rates of morbidity and mortality in NICUs. The estimated incidence varies between 5 and 170 per 1000 births, depending on the social context. In very low birth-weight neonates, the level of mortality increases with the duration of hospitalization, reaching 36% among infants aged 8–14 days and 52% among infants aged 15–28 days. Early diagnosis is the only tool to improve the poor prognosis of neonatal sepsis. Blood culture, the gold standard for diagnosis, is time-consuming and poorly sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 66 publications
0
20
0
4
Order By: Relevance
“…Previously published data supported the use of P-SEP in the diagnosis of EOS, suggesting its similar or higher diagnostic accuracy compared to other markers of inflammation (25,26). However, conflicting results were reported on whether P-SEP alone may be sufficient in the diagnosis of EOS (27) or whether it may be used to better advantage in combination with other inflammatory markers (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published data supported the use of P-SEP in the diagnosis of EOS, suggesting its similar or higher diagnostic accuracy compared to other markers of inflammation (25,26). However, conflicting results were reported on whether P-SEP alone may be sufficient in the diagnosis of EOS (27) or whether it may be used to better advantage in combination with other inflammatory markers (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Algo importante a destacar sobre o presepsina é que, ao contrário de outros biomarcadores e do método utilizado para a medição final, que pode ser ELISA ou ECLIA, foi observada uma redução considerável no tempo que leva para obter os resultados, com o método ELISA levando uma hora e meia e o método ECLIA obtendo resultados em 17 minutos quando 6 amostras são avaliadas simultaneamente (Galliera et al, 2019;Hung et al, 2020;Maddaloni et al, 2021).…”
Section: Biomarcador Cd14 Solúvelunclassified
“…Com relação ao mecanismo de produção da presepsina, é importante saber de onde ela se origina, já que a presepsina é uma das formas em que o CD14 é expresso. O CD14 é uma glicoproteína pertencente à família Toll-like receptor (TLR) que é expressa na superfície de monócitos e macrófagos; O CD14 tem duas formas de expressão, uma de membrana (mCD14) e a solúvel CD14 (sCD14), sendo esta última a que será observada no plasma devido ao aumento da secreção celular pelo hepatócito ou diminuição do mCD14 (Koh et al, 2021;Maddaloni et al, 2021;Mwesigye et al, 2021). O CD14 se liga principalmente a um complexo formado por bactérias lipopolissacarídeo (LPS) e proteína de ligação de lipoproteínas (LBP).…”
Section: Biomarcador Cd14 Solúvelunclassified
See 1 more Smart Citation
“…It is not affected by perinatal factors or gestational age. Three recent meta-analyses reported that presepsin has a pooled sensitivity ranging between 81% and 93% and a pooled specificity between 86% and 91% [ 79 , 80 , 81 ]. Another good marker is SAA, which is an acute-phase protein produced in response to IL-6.…”
Section: Newborn Perspectivementioning
confidence: 99%